Content Analysis of Online English Newspapers in India - Haneefa, Mohamed; Nellikka, Shyma (DESIDOC Journal of Library & Information Technology, 2010)
This paper aims to provide an overview of the contents and design of the online English newspapers in India. The study used website content analysis to assess the contents and design of the online English newspapers. Twelve online English newspapers published daily in India were selected for the study. A checklist was developed as the main tool for data collection. Microsoft Excel was used as the tool for data analysis. The study shows that online English newspapers in India have a common pattern of contents, coverage and design. Contents availability and access to the contents are the most prevalent options in these newspapers. Majority of the newspapers use Blog, RSS and Facebook to connect with their readers. Cost-benefit analyses and reader studies should be undertaken in order to optimize the performance of each online newspapers. This paper is useful for evaluating online newspapers and news sites. DOI: 10.14429/djlit.30.292